Conflict processing among multiple frames of reference. Issue 4 (December 2016) - Nan, Weizhi; Li, Qi; Sun, Yanlong; Wang, Hongbin; Liu, Xun
Abstract: People rely on multiple frames of reference (FORs) to represent and update spatial relationships of different objects in a complex environment. According to the "Frame of Reference‐based Map of Salience" theory (FORMS), FORs with high salience are processed in priority, and human performance is determined by the interaction of all relevant FOR‐based representations. We conducted a modified two‐cannon task manipulating conflicts among FORs (e.g., egocentric [FOR‐EFOR], intrinsic [FOR‐IFOR]) in order to explore how FORs interact with each other. We found that participants responded slower when two IFORs were incongruent than when they were congruent. There was also an interaction between these two conflicts. Moreover, the effect size of conflict between two IFORs was much larger than that between an IFOR and an EFOR. These results suggest that although the IFOR and EFOR may be coded by different spatial representations, they rely on a common processing mechanism and compete with each other. The findings from the current study provide support for the FORMS theory.